ISLAMIC-BASED DEVELOPMENT FOR POST-TSUNAMI ACEH: A THEORETICAL CONSTRUCT - Muhammad Syukri Salleh (Sharia and Law Faculty, 2017)
This is a simple paper with a straight forward aim. It attempts to suggest a development design for post-tsunami Aceh based on Islam, the very faith of the majority of indigenous people in Aceh. In so doing, the paper is divided into three sections. The first is to express a conviction that the development of post-tsunami Aceh should be based on Islam as it is not only the religion of the majority of the indigenous, but also has proven to be workable and successful in the history of Aceh civilization. The second is to overview the state of the present development strategy of post-tsunami Aceh vis-Ã -vis the above conviction. And the third, finally, is to propose a theoretical construct of Islamic-based development strategy for the post-tsunami Aceh.